Hybrid interspaced and free-boundary aramid fabric back bumper for hypervelocity impact shielding system. (January 2023) - Sathish Kumar, Sarath Kumar; Kim, YunHo; Cha, Jihun; Kim, Chun-Gon
Highlights: Idea of varying the degree of freedom of Kevlar fabric back bumper is proposed. Interspaced and free-boundary fabric system showed improved energy absorption. A hybrid interspaced and free-boundary fabric system was designed. Hybrid fabric system shielding efficiency increased as impact velocity increases. Abstract: This study elaborated the mechanism whereby the hypervelocity impact shielding efficiency of a stuffed Whipple shield design can be enhanced by improving the energy absorption of a fabric back bumper. Two system designs, an interspaced fabric system and a free-boundary fabric system, were discussed and studied in terms of their hypervelocity impact performance at approximately 3.8 km/s. Both the fabric systems were found to increase the energy absorbed by the back bumper compared to the conventional fabric system. Consequently, a hybrid fabric system, incorporating both the interspaced and free-boundary fabric systems, was designed based on the experimental observations from conventional and the aforementioned fabric systems, and the hypervelocity impact performance of this hybrid bumper was evaluated at different impact velocities. The experiments showed that the hybrid back bumper fabric system exhibited significantly improved energy absorption, thus improving the shielding efficiency of the Whipple shield at higher velocities.